2018
DOI: 10.1177/1077699018804500
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of News Media’s Public Agenda-Setting Effects, 1972-2015

Abstract: This study used rigorous meta-analytic approaches to analyze empirical agenda-setting studies published from 1972 to 2015, and 67 studies that met the inclusion criteria for analysis produced a moderate grand mean effect size of 0.487. A multiple regression analysis revealed one most notable predictor that classified the basis for the study correlation as either content categories or survey participants. A multiple regression of a subgroup using content categories produced homogeneity. The mean effect size for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 56 publications
2
39
0
3
Order By: Relevance
“…In addition, Wu and Coleman (2009) proposed the “hierarchy of effects theory,” suggesting that the second-level agenda (attribute) has more effects on influencing the public agenda than the first-level agenda (issue). However, Luo et al (2019) used a meta-analysis of agenda-setting and suggested that both the first-level and second-level agenda setting were equally powerful in influencing the public perception of the issues and their attributes. An increasing number of empirical studies have incorporated agenda-setting theory across a variety of media, including newspapers (Tam, 2015), online media (Roberts et al , 2002) and social media (Vogler and Eisenegger, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Wu and Coleman (2009) proposed the “hierarchy of effects theory,” suggesting that the second-level agenda (attribute) has more effects on influencing the public agenda than the first-level agenda (issue). However, Luo et al (2019) used a meta-analysis of agenda-setting and suggested that both the first-level and second-level agenda setting were equally powerful in influencing the public perception of the issues and their attributes. An increasing number of empirical studies have incorporated agenda-setting theory across a variety of media, including newspapers (Tam, 2015), online media (Roberts et al , 2002) and social media (Vogler and Eisenegger, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing number of empirical studies have incorporated agenda-setting theory across a variety of media, including newspapers (Tam, 2015), online media (Roberts et al , 2002) and social media (Vogler and Eisenegger, 2020). Compared to other types of media, newspapers have stronger agenda-setting effects on shaping public perceptions (Luo et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Valkenburg, Peter, and Walther [ 37 ] concluded that meta-analyses typically report small to moderate media effects under r = 0.20. Luo, Burley, Moe, and Sui [ 42 ] analyzed 43 years of agenda-setting studies and found a moderate mean effect size of 0.487. Such limited effects suggest that media use or attention should probably be viewed and tested as a potential moderator instead of a direct, independent variable.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The importance of the agenda-setting theory has not waned. Recent studies show how the relevance that the media give to an issue determines the audience's attention [18] and its perception even in international affairs in the current multiplatform and multimedia media context. However, it is always necessary to consider the audience's awareness of media's power [19].…”
Section: Introductionmentioning
confidence: 99%